Possibilidades de atuação do Núcleo Ampliado de Atenção à Saúde da Família e Atenção Básica na gestão do cuidado à criança com doença crônica - Santana, Renata Morais de (2020)
Introduction: The Family Health and Primary Care Extended Centers are consolidated in Primary Care in Brazil in order to guarantee the longitudinality of care through actions that directly impact people’s health conditions. Objective: To understand the actions of The Family Health and Primary Care in the management of care for children with chronic illness in Primary Health Care. Methodology: Research with a qualitative approach of an exploratory-descriptive nature. The study was carried out with health professionals who work in teams of the Family Health and Primary Care in a large municipality in Pernambuco. Data collection was performed using the focus group technique, in the months of February and April of 2019. The empirical material was interpreted through thematic analysis. Results: The matrix support bases the performance of the teams, such activities include both individual and collective care, with care management highlighted in all its dimensions, even if partially. The organizational and professional dimensions were positively highlighted with regard to the organization of formal flows of care and construction/strengthening of bonds based on integrated work between the teams involved. However, weaknesses in the systemic and societal dimensions were found when informal referrals from primary care to the specialized network were identified, compromising the referral and counter-referral process, and the absence of sufficient vacancies by the regulatory system of the studied municipality. Conclusion: The work of the Family Health and Primary Care Extended Centers with the Family Health Teams increases the possibility of expanded care in primary care, promoting new organizational formats of health care that favor the management of care for children with chronic health conditions.